Proposal for Supplier Relationship Management at PT XL Axiata Tbk - Pratama, Aji Nugraha; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
The telecommunication industry in Indonesia is growing rapidly in the last fifteen years. The habit slowly changed from voice and short messaging service into data. Nowadays, the challenge for the telecommunication company is to provide good quality of network. To fulfill the challenge, XL has been developing a partnerships scheme with suppliers and has been creating a performance measurement to keep partnerships work in the right path. The last supplier performance measurement report shows that the result is not meet the target. The unsatisfying result show that something wrong in the partnership with supplier. To find the core problem, this paper uses a Current Reality Tree (CRT) method. Based on CRT analysis, the core problem that arises is poor coordination. To eliminate core problem, a strategy is created. Strategic Supply Management is used as a framework to create strategy in eliminating core problem. Four critical enablers in the strategic supply management are analyzed to find solution for the problem. Those four critical enablers are organizational design, supply measurements, information systems, and human resources. The suggested and recommended solution based on analysis are improvement in business process, developing responsibility assignment matrix (RAM), create web-based application, and developing skill and knowledge people in supply organization.Keywords: telecommunication industry, supplier relationships, current reality tree, supply management